Rancang Bangun Sistem Informasi Kepegawaian Pada PT Radja Dagang Indonesia - Steven, Steven; Dafid, Dafid (Universitas Multi Data Palembang, 2024)
PT Radja Dagang Indonesia is a company that operates in the cement distributor sector, especially conch cement. PT Radja Dagang Indonesia has problems related to the employment process, such as the company not having data records for prospective employees, the process of applying for leave/permits which is still manual and also related to the absence of employees who are on assignment outside the city. Based on these problems, the solution given is to develop a personnel information system. The aim of creating this system is to help companies process personnel data effectively and efficiently, with the hope of reducing the potential for errors and data loss. This web-based application was created in the Visual Studio Code text editor with a MySQL database and the PHP programming language. The method used in creating this system is the RUP (Rational Unified Process) method which has 4 (four) phases, namely Inception, Elaboration, Construction, and Transition. The result of this final project is a website-based application that has recruitment features, attendance features, promotion features, demotion transfers, layoff features, leave features, reward & punishment features, assignment features that can help companies manage, and search for data more easily and quickly.